Chemical Castration Punishment Sanctions for Pedophilia Perpetrators in Indonesia - Burhanudin, Burhanudin (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
Chemical castration is an additional sanction for the criminal act of pedophilia contained in Law Number 17 of 2016 and Government Regulation Number 70 of 2020 as its implementing regulations. It is hoped that chemical castration will have a deterrent effect on pedophiles and can reduce the rate of sexual crimes in the future. However, on the other hand, chemical castration sanctions are considered a form of human rights violation. In Islamic law, the punishment of castration is based on al-maslahah, then the punishment of castration is recommended, whereas if it is based on al-maqassid as-syar-iyyah then the punishment of castration is not justified. The research method used is a normative juridical qualitative method with a statutory approach and a literature approach. The data sources used are secondary data in the form of child protection laws and implementing regulations, namely Government Regulation Number 70 of 2020. The results of the research state that the implementation of chemical castration sanctions is contrary to human rights and is not recommended in Islamic law because it can use criminal sanctions that are other.